FUTURISTIC & NOVEL CHALLENGES OF PERSONIFICATION OF AI: POST COVID. - Bharti, Piyush; Kumari, Prachi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Post demonetisation, the sudden outbreak of novel coronavirus took the globe by storm. Aftermath, it left evil impacts on the economy, and social life was not just enough; it also impacted the work of legal sectors. Parallel to this digitalisation, another development of artificial intelligence is going on. Can AI become the alternative to digitalisation, especially during a pandemic like COVID-19? How can AI aid digitalisation and prevent fraud, scams, discrimination, etc.? These have also broadened the scope of personification of machinery and legal liability and regulation of intelligent beings under the present legal system. Due to the Large Language Mode (LLM), the requirement of a new pronoun for AI to distinguish it from a human being for security and protection of rights and ethics was recently questioned. With ethical and moral challenges, the consequences of the development of Generative AI are another point of debate now. Recently, the CHAT GPT has been blocked by major news agencies and newspapers like The New York Reuters and CNN due to monetary losses and IPR violations. In India, several news channels have introduced AI-based news anchors. On the other hand, one tiding recently showed that AI cameras had been used to catch the vehicles of VIPs, including MPs and MLAs, for serious traffic offences. The health ministry used AI to tackle millions of frauds in the Ayushman Bharat. However, several high courts disagreed with accepting AI as the basis for adjudicating legal issues. How to regulate AI is a crucial issue for the Indian Legal System.